Executive functions in obsessive–compulsive disorder: An activation likelihood estimate meta-analysis of fMRI studies - Del Casale, A; Rapinesi, C; Kotzalidis, G; De Giorgi, R; al., E (Taylor and Francis, 2015)
Objectives: To identify activation changes assessed in functional magnetic resonance imaging (fMRI) studies of obsessive–compulsive disorder (OCD) through Activation Likelihood Estimate meta-analysis. Methods: We included 28 peer-reviewed standard stereotactic space studies assessing adult OCD patients (OCDpts) vs. healthy controls (HCs) with fMRI during executive task performance. Results: In within-group analyses, HCs showed task-related activations in bilateral inferior frontal gyri, right middle frontal gyrus, right inferior parietal lobule, right claustrum, bilateral cingulate gyri, and left caudate body. OCDpts showed task-related left-sided activations in the superior, medial, and inferior frontal gyri, and thalamus, and bilateral activations in the middle frontal gyri, inferior parietal lobule, and insular cortices. Subtraction analysis showed increased left middle frontal gyrus activation in OCDpts. In between-groups analyses, OCDpts hypoactivated the right caudate body, left putamen, left ACC, and right medial and middle frontal gyri. Right caudate hypoactivation persisted also after applying Family‐wise error algorithms. Conclusions: This meta-analysis confirms that during executive functioning OCDpts show a functional deficit of the right caudate body, which could represent a major neural functional correlate of their illness.